2020
DOI: 10.2147/cmar.s237300
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safety and Efficacy of PD-1 Inhibitors Plus Chemotherapy in Advanced Soft Tissue Sarcomas: A Retrospective Study</p>

Abstract: Purpose: Programmed cell death 1 (PD-1) inhibitors are ineffective as monotherapy for the treatment of soft tissue sarcomas (STS). However, increasing evidence shows that the combination of PD-1 inhibitors and chemotherapy is efficacious and safe for many types of malignancies, including STS. This study aimed to assess the safety and efficacy of doxorubicin chemotherapy plus PD-1 inhibitor in the treatment of metastatic STS. Patients and Methods: We retrospectively reviewed 21 patients with metastatic STS who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Compared with that noted in previous studies on doxorubicin-based chemotherapy in sarcoma, the efficacy of the combination therapy in this study was significantly improved in UPS and dedifferentiated liposarcoma ( McGovern et al, 2017 ; Seddon et al, 2017 ). Notably, previous studies have also demonstrated the efficacy of the PD-1 inhibitor plus doxorubicin in UPS and dedifferentiated liposarcoma ( Tian et al, 2020a ; Pollack et al, 2020 ; Livingston et al, 2021 ). This suggests that the PD-1 inhibitor plus doxorubicin may be the most effective treatment for these two sarcoma subtypes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Compared with that noted in previous studies on doxorubicin-based chemotherapy in sarcoma, the efficacy of the combination therapy in this study was significantly improved in UPS and dedifferentiated liposarcoma ( McGovern et al, 2017 ; Seddon et al, 2017 ). Notably, previous studies have also demonstrated the efficacy of the PD-1 inhibitor plus doxorubicin in UPS and dedifferentiated liposarcoma ( Tian et al, 2020a ; Pollack et al, 2020 ; Livingston et al, 2021 ). This suggests that the PD-1 inhibitor plus doxorubicin may be the most effective treatment for these two sarcoma subtypes.…”
Section: Discussionmentioning
confidence: 93%
“…Although in this study, we deliberately chose to administer PD-1 inhibitor 48 h after the completion of chemotherapy, the overall efficacy did not seem to improve compared with that in other studies where PD-1 inhibitor was administered simultaneously with chemotherapy ( Tian et al, 2020a ; Pollack et al, 2020 ). This differs from studies that report that the timing of administration can significantly affect the efficacy of PD-1 inhibitors plus chemotherapy ( Yao et al, 2021 ; Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because camrelizumab is a new agent, there is no specific analysis of the causes and mechanisms of hypothyroidism. After searching the literature, we found that camrelizumab has been reported to have this risk, and we wait for the explanation of mechanism and confirmation of follow-up basic research (13,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are only a few clinical studies on the efficacy of PD-1/L1 inhibitor plus chemotherapy in sarcomas, some studies have reported improved efficacy (Table 2). At present, several retrospective studies have suggested that chemotherapy combined with PD-1 inhibitor has certain efficacy in soft tissue sarcomas (85)(86)(87). In these retrospective studies, each sarcoma subtype responded differently to the combination regimen.…”
Section: Research Evidence In Sarcomasmentioning
confidence: 99%